2014
DOI: 10.11144/javeriana.upsy13-3.emgd
|View full text |Cite
|
Sign up to set email alerts
|

¿Está mediada la gravedad delictiva y cronicidad de los delincuentes juveniles por la competencia cognitivo-comportamental?

Abstract: r e s u M e n El estudio de la relación de los problemas de conducta con la competencia cognitiva y comportamental se ha convertido en un referente continuo en la literatura científica. A este respecto, los modelos de Riesgo-NecesidadesResponsividad (RNR) y de la criminología del desarrollo prevén que el nivel de problemas de conducta esté asociado al grado de desarrollo de la competencia cognitiva y comportamental. Desde una perspectiva legal, los problemas de conducta se identifican con la delincuencia, esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
2
1
0
2
Order By: Relevance
“…Theses results, therefore, support the idea that there is a relationship between psychopathology and criminal conduct (Fariña, Arce, & Vázquez, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…Theses results, therefore, support the idea that there is a relationship between psychopathology and criminal conduct (Fariña, Arce, & Vázquez, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…Similar to the findings of present study, psychological instability was also found to be a characteristic of adolescents in foster care ( (Bastiaanssen, Delsing, Kroes, Engels, & Veerman, 2014). Moreover, deficiencies in these health markers have been found to be vehicles of recidivism (Basanta et al, 2018;Fariña et al, 2014;Novo et al, 2012). However, the magnitude of harm and its effect on mental health markers remains unclear.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, regarding the mechanisms by which violence exposure would influence the development of aggressive behaviors, social-cognitive processing variables could be crucial, as previous literature highlights the role of hostile attributions and the lack of social problem-solving skills in aggressive children who have been maltreated (e.g., Molina, & Cano, 2011;Dodge & Pettit, 2003). The lack of cognitive competence (i.e., social problem-solving skills, biases in attribution process), discriminating delinquent and antisocial adolescents from non-deviant ones (Arce, Fariña, & Vázquez, 2011) is also related with offence severity and chronicity in juvenile delinquency (Fariña, Arce, & Vázquez, 2014). Moreover, previous studies with legal and community samples in the field of CPV note the relevance of these variables in adolescents who assault their parents Calvete, Gámez-Guadix, & García-Salvador, 2014;Contreras & Cano, 2014a, 2015.…”
Section: Discussionmentioning
confidence: 99%